Pekar bipolaron and the virial theorem (arbitrary coupling) - Kashirina, N.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
The work is devoted to issues related with implementation of the virial theorem for one-center bipolaron. The virial theorem expressions have been obtained for an electron system with Coulomb interactions in the phonon field. It is shown that for the bipolaron functional (one-center configuration) virial theorem holds for arbitrary electron-phonon coupling. As a specific example of the virial theorem for one-center bipolaron configuration, the author adduces numerical calculations of the energy of the ground state and the various contributions (kinetic energy, electron-phonon interaction, electron energy, phonon energy) into the energy of bipolaron, performed within the framework of Buimistrov-Pekar method. It is shown that the virial theorem is fulfilled with high accuracy for the two-electron systems with Coulomb interactions for an arbitrary value electron-phonon coupling. The necessary condition for formation of a bipolaron stable state is accounting electron correlations associated with the direct dependence of the trial electron wave function of the system from the interelectron distance.